166k views
14 votes
I need help on 8 9 and 10

I need help on 8 9 and 10-example-1

1 Answer

3 votes

9. x + (y - 3 - 4x + 2( 3x - (-y - 1) + 2y) - 3x)

= x + (y - 3 - 4x + 2 (3x + y - 1) + 2y - 3x)
= x + (y - 3 - 4x + 6x + 2y - 2 + 2y - 3x)
= (x - 4x + 6x - 3x) + (y + 2y + 2y) - (3+2)
= 0 + 5y - 5
= 5y - 5 (or simplified as 5(y-1)

10. 6 + (-a -3(b + 6(a - b)+4a) - 2b)
= 6 + (-a - 3(b + 6a - 6b + 4a) -2b)
= 6 + (-a - 3b + 18a - 18b + 12a - 2b)
= 6 + (-a + 18a + 12a) + (-3b - 18b - 2b)
= 6 + 29a - 23b

Lmk if it's wrong, I'll try to edit it.

User Lakshman Diwaakar
by
5.0k points